2023
DOI: 10.1186/s12948-022-00182-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular sensitization pattern to house dust mites is formed from the first years of life and includes group 1, 2, Der p 23, Der p 5, Der p 7 and Der p 21 allergens

Abstract: Background As the process and nature of developing sensitivity to house dust mites (HDMs) remain not fully studied, our goal was to establish the pattern, nature and timeframe of house dust mite (HDM) sensitization development in patients in Ukraine as well as the period when treatment of such patients would be most effective. Methods The data of the multiplex allergy test Alex2 was collected from 20,033 patients. To determine age specifics of sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Previous papers used BN as a decision support system determining the skin 24,25 (and house dust mite sensitization). 26 However, application of Bayesian modelling for the healthcare systems seems to be useful and needs further clinical adoption 27 This was shown in this study as many of the patterns found by the BN are consistent with the known clinical data. For example, modelling suggested that while affecting the development of sensitization to other allergens, Phl p 2 itself was not affected by them.…”
Section: F I G U R Ementioning
confidence: 68%
See 1 more Smart Citation
“…Previous papers used BN as a decision support system determining the skin 24,25 (and house dust mite sensitization). 26 However, application of Bayesian modelling for the healthcare systems seems to be useful and needs further clinical adoption 27 This was shown in this study as many of the patterns found by the BN are consistent with the known clinical data. For example, modelling suggested that while affecting the development of sensitization to other allergens, Phl p 2 itself was not affected by them.…”
Section: F I G U R Ementioning
confidence: 68%
“…To our knowledge, this is the first paper in the world which uses a BN in order to establish the hierarchy in the sensitization to grass allergens. Previous papers used BN as a decision support system determining the skin 24,25 (and house dust mite sensitization) 26 . However, application of Bayesian modelling for the healthcare systems seems to be useful and needs further clinical adoption 27 …”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the prevalence of Der p 23 varied among patient cohorts 9,30–32 . A recent study conducted in Ukraine noted that sensitivity to Der p23 becomes evident in the first year of life 33 . This suggests that factors such as geographical region and age may significantly influence sensitization to Der p 23, while the prevalence of Der p 1 or Der p 2 is less affected 34 …”
Section: Discussionmentioning
confidence: 98%
“…9,30-32 A recent study conducted in Ukraine noted that sensitivity to Der p23 becomes evident in the first year of life. 33 This suggests that factors such as geographical region and age may significantly influence sensitization to Der p 23, while the prevalence of Der p 1 or Der p 2 is less affected. 34 In the Italian study by Celi et al, Der p 23 was identified as a risk factor for asthma, particularly severe asthma, 35 while Villalta found a stronger association between Der p 23 and rhinitis.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…8 While group A molecules (Der p 1, Der p 2, and Der p 23) have long been recognized as primary Der p sensitization triggers 6,[8][9][10] and have been at the epicenter of HDM epidemiological studies for many years, our knowledge on group B allergen (Der p 5, Der p 7, and Der p 21) prevalence is still lacking. 8,10,11 As sensitization patterns of mite-allergic patients are influenced by age, gender, heredity, and mite exposure 8,10 it is important to define Lithuanian population sensitization profiles to gain a better understanding of worldwide Der p sensitization trends. [12][13][14][15] The aim of this study was to assess the sensitization profiles to MA's derived from house dust mite (Dermatophagoides pteronyssinus) in the Lithuanian population.…”
Section: Introductionmentioning
confidence: 99%